HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN EXPLOSIVE POWER OTOT LENGAN-BAHU DENGAN AKURASI SMASH TEAM BOLA VOLI PUTRA BULOG PEKANBARU - Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Problems in the research starting from the observation that the author found in the field,. researchers find flaws on the results smash a less loud, visible when the leap yet nice and hard to hit the ball above the net, which result in accuracy results are not optimal. The purpose of this study is to find out the relationship yield limb muscles and the explosive power of shoulder-arm muscles with pinpoint accuracy smash volleyball team son Bulog Pekanbaru. Population in this research is the son of volleyball athlete Bulog Pekanbaru and total them is 12 person used thecnique total sampling and all to be sample so not need test for t. And to be get of data for research used Vertical Jump test for explosive explosive tests of limb muscles, arm muscles power-shoulder Two-Hand Medicine Ball Putt, and accuracy Tests performed as many as 5 smash balls for accuracy. The data obtained were analysis with correlation product moment. On the analysis of data obtained correlation X1 with Y rhitung = 0.642 > rtabel = 0.602 and X2withY of rhitung = 0.651 > rtabel = 0.602 while the X1 and X2 with Y of rhitung = 0.683 > rtabel = 0.602. because all connect to shows in this research have significant level, then by doing so Ho and Ha rejected accepted. This means that there is an explosive relationship limb muscles and the explosive power of shoulder-arm muscles with pinpoint accuracy smash volleyball team son Bulog Pekanbaru. Where the conditions of the existence of a correlation variable with another variable that is determined from the rhitung > rtabelKey Words: Explosive Explosive Power Limb Muscles, Arm Muscles-The Shoulders,The Accuracy Of The Spike A Volleyball